Kinetic Isotope Effects (KIE) and Density Functional Theory (DFT): A Match Made in Heaven? - Christensen, Niels Johan; Fristrup, Peter (Synlett, 2015)
Determination of experimental kinetic isotope effects (KIE) is one of the most useful tools for the exploration of reaction mechanisms in organometallic chemistry. The approach has been further strengthened during the last decade with advances in modern computational chemistry. This allows for the calculation of a theoretical KIE that can often be compared directly to the experimental value. This combined experimental/theoretical approach can be particularly useful in cases where the value of the experimental KIE is not directly associated with one particular reaction step (e.g., in a catalytic reaction). The approach is highlighted by using recent examples from both stoichiometric and catalytic reactions, homogeneous and heterogeneous catalysis, and enzyme catalysis to illustrate the expected accuracy and utility of this approach.
Keywords: kinetic isotope effect; competition experiments; density functional calculations; catalysis